Rib Radiography versus Chest Computed Tomography in the Diagnosis of Rib Fractures - Sano, Atsushi (The Thoracic and Cardiovascular Surgeon, 2018)
Background The accurate diagnosis of rib fractures is important in chest trauma. Diagnostic images following chest trauma are usually obtained via chest X-ray, chest computed tomography, or rib radiography. This study evaluated the diagnostic characteristics of rib radiography and chest computed tomography.Methods Seventy-five rib fracture patients who underwent both chest computed tomography and rib radiography between April 2008 and December 2013 were included. Rib radiographs, centered on the site of pain, were taken from two directions. Chest computed tomography was performed using a 16-row multidetector scanner with 5-mm slice-pitch without overlap, and axial images were visualized in a bone window.Result In total, 217 rib fractures were diagnosed in 75 patients. Rib radiography missed 43 rib fractures in 24 patients. The causes were overlap with organs in 15 cases, trivial fractures in 21 cases, and injury outside the imaging range in 7 cases. Left lower rib fractures were often missed due to overlap with the heart, while middle and lower rib fractures were frequently not diagnosed due to overlap with abdominal organs. Computed tomography missed 21 rib fractures in 17 patients. The causes were horizontal fractures in 10 cases, trivial fractures in 9 cases, and insufficient breath holding in 1 case.Conclusion In rib radiography, overlap with organs and fractures outside the imaging range were characteristic reasons for missed diagnoses. In chest computed tomography, horizontal rib fractures and insufficient breath holding were often responsible. We should take these challenges into account when diagnosing rib fractures.
Keywords: rib fracture; computed tomography; rib radiography; chest trauma